Expanded molecular phylogeny of the genus Bicyclus (Lepidoptera: Nymphalidae) shows the importance of increased sampling for detecting semi-cryptic species and highlights potentials for future studies. Issue 2 (4th March 2017) - Aduse-Poku, Kwaku; Brakefield, Paul M.; Wahlberg, Niklas; Brattström, Oskar
Abstract : The genus Bicyclus is one of the largest groups of African butterflies, but due to the generally cryptic nature and seasonal variation of adult wing patterns, there has been a lot of systematic confusion. With a large research community working with the model species Bicyclus anynana there has been increasing interest in the evolutionary history of the genus. A previous phylogeny started to unravel interesting patterns, but only included 61% of the then known species. With a range of new species having been described in the last decade there has been a need for an updated phylogeny for the genus. We present the most complete phylogeny of Bicyclus yet, including 93% of the currently 103 recognized species and make a range of taxonomic revisions. We revise the status of four previous subspecies and synonymized taxa that in the light of the new genetic data are raised to species level. We also subsume two subspecies and describe a new species, Bicyclus collinsi sp. nov., based on both genetic and morphological evidence. A further new taxon is identified, but not described at this point due to lack of morphological data. Our phylogeny lays a solid foundation for better understanding the evolution of Bicyclus and highlights key species-groups and complexes with intriguing ecological patterns making them prime candidates for future studies. http://zoobank.org/urn:lsid:zoobank.org:pub:2F775351-097E-4CD7-8F8F-A90B26D52DE8